Effect of Green Tea on the Level of Salivary Interleukin-1 Beta in Patients with Chronic Periodontitis: A Randomized Clinical Trial. (6th June 2022) - Rezvani, Gita; Taleghani, Ferial; Valizadeh, Maryam
Abstract : Aim . Interleukin-1 beta (IL-1 β ) is one of the major biomarkers involved in the pathogenesis of chronic periodontitis. The aim of this study was to evaluate the changes in salivary IL-1 β concentration in patients with chronic periodontitis following daily consumption of green tea. Methods and Materials . Thirty patients with an average age of 45.8 years suffering from chronic periodontitis were randomly assigned into 2 groups (i.e., experimental and control groups). Besides receiving phase 1 periodontal treatment (scaling and root planning (SRP)), the experimental group drank green tea for a period of 6 weeks. To measure the concentration of salivary IL-1 β, saliva samples were taken from both groups at 2 time points, i.e., prior to SRP (time point 1 (T0)) and after 6 weeks (time point 2 (T1)). The nonparametric Wilcoxon test was used to examine and compare the changes in the concentration of salivary IL-1 β in each group relevant to the 2 time points (T0 and T1). Data were submitted to statistical analysis. Results . At the end of the study period, a significant reduction (P = 0.0001 ) in the concentration of salivary IL-1 β was observed in the experimental group ( A ). As for the control group ( B ), however, there was no significant change (P = 0.307 ) in the concentration of salivary IL-1 β after 6 weeks following phase 1 periodontal treatment. Conclusion . Green tea supplementation, in addition to SRP, may reduce salivary IL-1 β levels in patients with chronic periodontitis for a period of 6 weeks.